Measurement of the $Y(1S), Y(2S)$ and $Y(3S)$ polarizations in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2183 authors) (2013)
The polarizations of the Y(1S), Y(2S), and Y(3S) mesons are measured in proton-proton collisions at sqrt(s) = 7 TeV, using a data sample of Y(nS) to oppositely charged muon pair decays collected by the CMS experiment, corresponding to an integrated luminosity of 4.9 inverse femtobarns. The dimuon decay angular distributions are analyzed in three different polarization frames. The polarization parameters lambda[theta], lambda[phi], and lambda[theta,phi], as well as the frame-invariant quantity lambda-tilde, are presented as a function of the Y(nS) transverse momentum between 10 and 50 GeV, in the rapidity ranges abs(y) < 0.6 and 0.6 < abs(y) < 1.2. No evidence of large transverse or longitudinal polarizations has been seen in the explored kinematic region.